Correlation of Fc-γ RIIA polymorphisms with latent Epstein–Barr virus infection and latent membrane protein 1 expression in patients with low grade B-cell lymphomas. Issue 9 (September 2013) - Diamantopoulos, Panagiotis T.; Kalotychou, Vassiliki; Polonyfi, Katerina; Sofotasiou, Maria; Anastasopoulou, Amalia; Galanopoulos, Athanassios; Spanakis, Nikolaos; Vassilakopoulos, Theodoros; Angelopoulou, Maria; Siakantaris, Maria; Variami, Eleni; Poziopoulos, Christos; et al.
Abstract: Fc-γ RIIA (CD32), a member of the family of Fc-γ receptors, participates in the phagocytosis of bound to antibody antigens. The effectiveness of this function varies for its several haplotypes, and it participates in the pathogenesis of viral infections, according to recent studies. The genetic locus of Fc-γ RIIA consists of two allelic genes: 131-Arg (R131) and 131-His (H131). Our aim was to correlate Fc-γ RIIA polymorphisms, by studying the prevalence of each allele using PCR-RFLPs (polymerase chain reaction-restriction fragment length polymorphisms), with latent Epstein–Barr virus (EBV) infection and the expression of latent membrane protein 1 (LMP1) in 40 patients with leukemic low grade B-cell lymphomas. R131 was found in 84.2% of EBV-positive patients, but only in 28.5% of EBV-negative patients ( p = 0.001). A similar correlation was found for R131 and LMP1 expression (84.6% vs. 28.5%) ( p = 0.002). Our results support the hypothesis that Fc-γ RIIA polymorphisms are a genetic risk factor for latent EBV infection and the expression of its oncogenic latency proteins.